The use of social networking sites for language practice and learning - Baralt, Melissa (2011)
Recent descriptions of online social networking communities (i.e., Facebook, MySpace) within the Web 2.0 movement havesuggested that these sites might be used in educational contextsto promote cultural awareness, interaction, and collaboration(Ferdig et al., 2007). Here it is argued that social networkingsites can also be used for language teaching and learning. Thepurpose of this paper is therefore threefold: (1) to provide atheoretical framework justifying the use and incorporation ofsocial networking sites in foreign language courses; (2) to reviewexisting social networking sites and provide suggestions forhow they might be used in different language contexts; and (3)to describe an ongoing study in which one social networkingsite, Orkut, is being used for a course in Portuguese as a foreignlanguage. Besides suggesting that social networking sites canserve as an authentic way to be exposed to language and cultureoutside of the classroom, it is also argued that participation insocial networking sites can be an ideal medium for languagepractice and learning.